JCI Under Macroeconomic Pressure: The Moderating Role of Interest Rates on Inflation and Exchange Rates - Irma Nur Halimah; Sustari Alamsyah; Dhea Zatira (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of inflation, exchange rates, and interest rates on the Jakarta Composite Index (JCI), as well as to examine the role of interest rates as a moderating variable in these relationships. This research employs monthly time-series data from 2020-2024 obtained from the Indonesia Stock Exchange and Bank Indonesia. The analytical methods used include multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that inflation, exchange rates, and interest rates individually have a significant effect on the JCI. However, the moderation test reveals that interest rates are not able to significantly strengthen or weaken the relationship between inflation and exchange rates with the JCI. These findings suggest that the Indonesian capital market is more responsive to direct macroeconomic variables rather than the interaction effects among them. This study contributes to the literature on stock market behavior in emerging markets and provides insights for investors and policymakers in responding to global economic volatility.